Myopic progression in school-aged children with moderate intermittent exotropia - Shen, Tao; Liang, Mintong; Chen, Linxing (Frontiers in Pediatrics, 2023)
Objective: It is still controversial whether intermittent exotropia (IXT) affects myopic progression during the critical period of visual development. This study retrospectively analyzed the long-term myopic changes and the impact of IXT surgery on myopic progression in school-aged children with moderate IXT. Methods: The medical records of 65 children from 5 to 13 years old with or without IXT between 2015 and 2021 were retrospectively reviewed. Patients whose spherical equivalent refraction (SER) were less than -3.00 diopter (D) were included and divided into three groups: IXT surgery group (Group A), which comprised 22 IXT patients who received IXT surgery, IXT observation group (Group B), which comprises 19 IXT patients who only received long-term observational follow-up; and normal control group (Group C), which comprised 24 normal controls without IXT. The main outcome measurement was the rate of myopic progression, which was defined as the mean myopic shift in SER per year. Results: The 3- and 5-years long-term follow-up rates of myopic progression were -0.47±0.28 D per year and -0.48±0.23 D per year respectively in Group B, and those were significantly slower than that in Group C (-0.73±0.32 D per year and -0.76±0.19 D per year respectively). However, there was no significant difference in the rate of myopic progression between Group A and B or between Group A and C. Conclusion: Moderate IXT may have lower rate of myopic progression in school-aged children. Whether IXT surgery influence the rate of myopic progression still needs further study.